THE INFLUENCE OF VALUE ORIENTATIONS ON PSYCHOSOCIAL ADAPTATION OF ADOLESCENTS - Paladi, Oxana (International Journal of Innovative Technologies in Social Science, 2022)
The article presents the authors' conceptions regarding value orientations and psychosocial adaptation of personality; there are presented some results obtained in the carried out research with reference to the impact of value orientations on psychosocial adaptation in adolescence. There are briefly presented both, levels of manifestation of psychosocial adaptation in adolescence and priority value orientations (terminal and instrumental) for subjects who show a high level of psychosocial adaptation. At the same time, there are described indices of correlation coefficient regarding identification of the relationship between psychosocial adaptation and value orientations. The paper presents details regarding application of the linear regression method useful in verifying predictive, explanatory models in the research by which we determined to what extent value orientations influence psychosocial adaptation in adolescence. Moreover, the research results provided the opportunity to highlight the relationship between psychosocial adaptation and value orientations, which led to the outline of the Explanatory model of relationship between value orientations and psychosocial adaptation in adolescence.